PENGARUH DIAMETER LUBANG, JARAK LUBANG, DAN POSISI LUBANG FLUIDISASI DENGAN ALIRAN PERMUKAAN PADA METODE FLUIDISASI (Influence of Perforation diameter, Distance and Position on Bed Fluidization Method with Current) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Problem on river mouth and navigation channel is caused by sediment accumulation on the river mouth and navigation channel. Sedimentation pattern and process on river estuary and navigation channel are influenced by bed sediment, current, and marine hydro dynamic. Remedial solution that is generally performed is relatively expensive. Fluidization method can be an economical alternative for overcoming the problem on river mouth and navigation channel. The goal of this research is to evaluate the influence of fluidization variables such as perforation diameter (di), perforation distance (a) and perforation position (a), on the fluidization system. The research with physical model test was carried out at Hydraulic and Hydrology Laboratory, Research Centre for Engineering Science Gadjah Mada University. It comprises of three studies : fluidization basic study, influence among parameters, and case study on Sambong estuary. Basic research of fluidization was conducted using variation of sediment thickness (db), tube diameter (D). The effect among parameters was investigated by varying perforation diameter (df), perforation distance (a), perforation position (a), and sediment thickness (db). The case study on Sambong estuary was conducted using scale model of 1:12 .